MORPHOLOGICAL STUDY OF ADRENAL GLAND IN PRENATAL AND POSTNATAL PERIODS OF DOMESTIC RABBIT (ORYCTOLAGUSCUNICULUS) - Farhan Owda Rabie (Basrah Journal of Veterinary Research)
The developmental study of adrenal gland has been done on the local rabbit fetuses and neonate, which including a morphological and histological description of the adrenal gland. The study revealed that the differentiation of the adrenal gland began in the rabbit between twenty two and twenty four days from pregnancy as adrenal cortex and medulla and relatively completed it is histologically pictures at twelve days old. Also the study showedthat the adrenal cortex composed of three zones: zonaglomerulosa or the zonaarcuata , the zona fasciculate and the zonareticularisglomerulus, whilethe medulla have dark and light cells.The purpose of our study was to provide a more complete quantitive description of the histomorphology of the adrenal gland in rabbits during prenatal and postnatalperiods.